Familial clustering of tic disorders and obsessive-compulsive disorder - Browne, Heidi A; Hansen, Stefan N; Buxbaum, Joseph D; Gair, Shannon L; Nissen, Judith B; Nikolajsen, Kathrine H; Schendel, Diana E; Reichenberg, Abraham; Parner, Erik T; Grice, Dorothy E (JAMA psychiatry (Chicago, Ill.), 2015)
Tourette syndrome/chronic tic disorder (TS/CT) and obsessive-compulsive disorder (OCD) overlap in their phenomenological features and often co-occur in affected individuals and families. Understanding how these disorders cluster in families provides important clinical information and is an important step in understanding the causes of these disorders. To determine familial recurrence for TS/CT and OCD using a national epidemiologic sample. We performed a population-based study of national health registries in Denmark, including all individuals (n = 1 741 271) born in Denmark from January 1, 1980, through December 31, 2007, and followed up through December 31, 2013. We identified those with TS/CT and/or OCD. The prevalence of TS/CT and OCD and relative recurrence risk (RRR) for TS/CT or OCD among individuals with an oldest sibling or a parent diagnosed as having TS/CT or OCD compared with individuals without an affected oldest sibling or an affected parent. In this sample, 5596 individuals were diagnosed as having TS/CT; 6191, OCD; and 412, both disorders. The overall cohort prevalence of TS/CT was 0.42% (95% CI, 0.41%-0.43%) and of OCD, 0.84% (95% CI, 0.81%-0.87%). The mean sibling recurrence risk for TS/CT across all birth years was 9.88% (95% CI, 8.02%-12.16%) and for OCD, 4.01% (95% CI, 2.78%-5.76%). The sibling RRR for TS/CT was 18.63 (95% CI, 15.34-22.63). In contrast, the sibling RRR for OCD was 4.89 (95% CI, 3.45-6.93). The parent-offspring RRR for TS/CT was 61.02 (95% CI, 44.43-83.82), whereas the parent-offspring RRR for OCD was 6.25 (95% CI, 4.82-8.11). The sibling and parent-offspring cross-disorder risks were also significant, ranging from 3.20 (95% CI, 2.22-4.62) to 10.27 (95% CI, 5.17-20.39). Tourette syndrome/CT and OCD cluster in families. The familial aggregation of TS/CT is profound and substantially higher than the familial aggregation for OCD. The recurrence risk estimates provide an important clinical framework for identifying individuals at risk and provide insights into the causes of these disorders.